Leafcutting Bees, Megachilidae (Insecta: Hymenoptera: Megachilidae: Megachilinae) - David Serrano (EDIS)
Leafcutting bees are important native pollinators of North America. They use cut leaves to construct nests in cavities (mostly in rotting wood). They create multiple cells in the nest, each with a single larva and pollen stored for the larvae to eat. Leafcutting bees are important pollinators of wildflowers, fruits, vegetables and other crops. Leafcutting bees, Osmia spp. are even used as commercial pollinators (like honey bees) in crops such as alfalfa and blueberries. This document is EENY-342, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2005.